Inductive mechcharger: mechanical phone charging dock using faraday's law - Esham, Fahmi Ezzuddin; Zulkiflli, Nur Amira; Thamilvanan, Mathiventtan; Zulkifle, Nurul Afiqah; Raihansyah, Mochammad Azriel; Abdullah, Fatin Aliah Phang; Nawi, Nina Diana; Yoong Kang, Adam Wong; Abdullah, Jamel; Tee, Kian Sek; Mohamad, Elmy Johana; Pusppanathan, Jaysuman; et al. (Penerbit UTHM, 2022)
Energy and the environment are the key issues of the world in recent decades Requests for the quest for alternative energy sources has become a response to rising energy sources science and technology one of the top priorities. Over 90% of the global population power produced is based on electromagnetic induction laws from faraday. Thus, Free Energy / Electricity interests are becoming popular. The definition of free energy is a misconception. Nothing like free energy is there. But if we use tools like Solar, Wind, Tidal, and Hydro-Electric to produce it, Geothermal is free of charge only after the initial cost of capital. After the fact, the produced energy is free, that the electricity created by these unorthodox methods of electrical power generation must not be compensated for. Therefore, for some time, the idea of electricity generation with magnets has been around. They are used to generate energy through their magnetic fields. These magnets are mounted in engine and generator cores. The basic theory of power generation lies in the magnetic effect. "When the vehicle rotates in a magnet field, a voltage is generated in the car." [1,2]